1995
DOI: 10.1093/ije/24.4.704
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Homocysteine and Coronary Heart Disease

Abstract: In the general population serum total homocysteine is an independent risk factor for CHD with no threshold level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
237
0
10

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(262 citation statements)
references
References 0 publications
15
237
0
10
Order By: Relevance
“…Interestingly, in a recent Norwegian study, it was shown a positive linear association between plasma tHcy levels and total serum cholesterol (Nyga Êrd et al, 1995). Other studies have shown similar results, but no biochemical explanation for this association has been presented (Arnesen et al, 1995;Messer, 1986;Molgaard et al, 1992;Wu et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, in a recent Norwegian study, it was shown a positive linear association between plasma tHcy levels and total serum cholesterol (Nyga Êrd et al, 1995). Other studies have shown similar results, but no biochemical explanation for this association has been presented (Arnesen et al, 1995;Messer, 1986;Molgaard et al, 1992;Wu et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
“…There is increasing evidence that elevated levels of plasma total homocysteine (tHcy) is an independent risk factor for cardiovascular diseases (Arnesen et al, 1995;Boushey et al, 1995;Malinov, 1994;Nyga Êrd et al, 1995;Nyga Êrd et al, 1997a;Perry et al, 1995;Stampfer et al, 1992;Ueland et al, 1992). Low levels of the vitamins folate, cobalamin and B-6 have been shown to be related to elevated levels of tHcy (Ubbink et al, 1993;Selhub et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…13 There are additional concerns regarding unmeasured and residual confounding due to dietary and other lifestyle factors associated with hyperhomocysteinaemia. 14,15 The findings from the small number of prospective studies that have addressed associations between tHcy concentrations and incident coronary heart diseases (CHD) or stroke are inconsistent [16][17][18][19][20][21][22] Homozygosity for a defective thermolabile variant of MTHFR, a common genetic polymorphism which results in hyperhomocysteinemia, has not been consistently linked with cardiovascular disease endpoints. 23,24 Although the importance of gene markers will vary depending on relevant environmental exposures, diet in this instance, the findings from gene association studies conducted to-date are distinctly unimpressive.…”
Section: Thcy and Cardiovascular Diseasementioning
confidence: 99%
“…Semelhante a estudos prévios, a concentração sérica de homocisteína total apresentou correlações positivas significantes com os níveis de pressão arterial (41,43) e com as concentrações séricas de triglicérides (44) e de ácido úrico (45). A função renal, que é um determinante importante dos níveis de homocisteína (16), foi avaliada neste estudo através da medida dos níveis de creatinina sérica, que não apresentaram alterações.…”
Section: Discussionunclassified